LINGUISTIC FEATURES OF AI-RELATED INSTRUCTIONAL DISCOURSE IN ENGLISH AND UZBEK - Tulanboev , Shokhsuvar (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article investigates the linguistic features of AI-related instructional discourse in English and Uzbek. The rapid development of artificial intelligence has produced new forms of human–machine communication in which users are guided through prompts, commands, recommendations, safety warnings, interface instructions, algorithmic explanations, and procedural texts. In this context, instructional discourse is no longer limited to traditional manuals or pedagogical explanations; it also includes digital commands, prompt-writing guidelines, chatbot interaction patterns, platform-based instructions, and AI system warnings. The study approaches AI-related instructional discourse as a specialized form of procedural and directive communication. It compares English and Uzbek examples in terms of lexical, morphological, syntactic, semantic, and pragmatic features. The findings show that both languages rely heavily on imperative structures, sequential organization, technical terminology, modal expressions, and directive speech acts. However, English AI instructions tend to be more compact, verb-initial, and analytically organized, while Uzbek instructions are more morphologically explicit, politeness-oriented, and frequently constructed through verbal suffixes, auxiliary forms, and explanatory components. The article also demonstrates that Uzbek AI discourse is characterized by active borrowing, transliteration, calquing, and semantic adaptation of English AI terms such as prompt, chatbot, algorithm, machine learning, and neural network. The paper concludes that AI-related instructional discourse represents an emerging area of comparative linguistics, terminology studies, pragmatics, and digital discourse analysis.